Pelatihan Dan Pengenalan Terapi Komplementer Akupressure Sebagai Pendamping Pengendalian Hipertensi Di Wilayah Banjarbaru Selatan - -, Muhammad Rasyid; Hammad; Akhmad Rizani (UPPM Poltekkes Kemenkes Banjarmasin, 2024)
High prevalence of hypertension as a disease that is often undiagnosed or poorly uncontrolled has become a serious concern in the health sector. According to Riskesdas data in 2018, there was an increase in the prevalence of hypertension around 8.3%, where in 2018 the prevalence was 34.1% after previously in 2013 the prevalence was 25.8%. Hypertension or high blood pressure can be a serious trigger for various health problems including heart disease, stroke, and other circulatory disorders. Although medical treatment is still the main intervention, complementary approaches is also becoming increasingly important. One of the complementary therapies that can be used is the acupressure therapy. Acupressure is a therapy that can be done by applying pressure and massage to certain points on the body which is based on acupressure technique. The aim of this community service is to increase community knowledge, understanding, and skills in integrating acupressure therapy as a complementary approach for controlling hypertension. The target of this community service are the Rina Karya Posbindu cadres, Pandawa Posbindu cadres and traditional masseus in the working area of Banjarbaru Selatan Community Health Center, Guntung Paikat-district. The activities which is carried out during 3 times include providing health education, acupressure practice skill and evaluating the knowledge and skills of participants to do acupressure therapy for hypertension. The results of this community service are that after carrying out community service for 3 times, every participants have better knowledge, understanding and skills than before the community service was carried out. All participants have been able to determine acupressure points for hypertension and are able to perform acupressure techniques at these points.